2022
DOI: 10.1525/nr.2022.26.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Reasoned Flights beyond Reason

Abstract: New religious movements in modern western culture often emphasize experience at the expense of reason; for that reason, some scholars have described their teachings as “flights from reason.” This description has been rightly criticized. Nevertheless, it is not entirely wrong. Many founders of new religious movements do claim immediate insight into a (divine) reality that transcends the intellect. And yet, they and their followers often spend much of their lives building an intellectual frame around this anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a later study, they tempered their bold statement: "the claim that a spiritual revolution has taken place is exaggerated. Nevertheless, we have demonstrated that a major shift has occurred in the sacred landscape since the fifties and sixties, and is still continuing"(Heelas & Woodhead, 2005, p. 149).14 Much of this entails what I call "reasoned flights beyond reason"(Vliegenthart, 2022).…”
mentioning
confidence: 95%
“…In a later study, they tempered their bold statement: "the claim that a spiritual revolution has taken place is exaggerated. Nevertheless, we have demonstrated that a major shift has occurred in the sacred landscape since the fifties and sixties, and is still continuing"(Heelas & Woodhead, 2005, p. 149).14 Much of this entails what I call "reasoned flights beyond reason"(Vliegenthart, 2022).…”
mentioning
confidence: 95%